Maria sebagai Teladan Keselamatan : Pandangan Mariologi dalam Konteks Ende-Lio (Pusat Riset dan Inovasi Nasional, 2026)
This paper explores the role of Mary as a model of salvation in Catholic faith, focusing on the understanding of Mariology within the cultural context of the Ende-Lio people in Flores, East Nusa Tenggara. Mary is regarded not only as the Mother of Jesus Christ but also as an example of faith marked by humility, obedience, and hope. Her humility and willingness to accept God’s will, especially in the Annunciation, serve as a concrete inspiration for Catholics to respond faithfully to God’s call. Within the Ende-Lio culture, which values loyalty, solidarity, respect for ancestors, and harmony with nature, Mary becomes a figure closely connected to daily life. Devotions such as the rosary, pilgrimages to Marian grottoes, and the celebration of the Marian months highlight Mary’s living presence in both the faith and cultural traditions of the community. Thus, Mary serves as a bridge between the Gospel and local culture, revealing a Church that is rooted in its own soil yet remains faithful to Christ. This reflection affirms that contextual faith is a living faith deeply rooted in local culture while open to the saving work of God.